Analisis Kenyamanan dan Kestabilan Kendaraan Roda Dua Dalam Tinjauan Satu Derajat Kebebasan - Pipit Wahyu Nugroho (Jurnal Energi dan Teknologi Manufaktur, 2018)
The two most important parameters in driving are comfort and stability. To get the best value from that parameter, then the role of the vehicle suspension system is very important to reduce the vibration due to road waves and keep the wheels sticking above the road. This study studied the effect of suspension type on comfort level and vehicle stability. The type of suspension is related to the value of spring stiffness and its damping value. While the vehicle is modeled in one degree of freedom. The test is carried out with vehicle loading including mass of vehicle and passenger for each type of suspension, ie soft, medium and hard. Vibration analysis is done using Matlab Simulink to get the acceleration response and its deflection response. The vibration response graph shows the comparison of comfort level and vehicle stability on the road profiles modeled in step, impulse, and sinusiodal functions. From the simulation results obtained that Soft and Medium Suspension can handle the vibration very well especially from the level of response speed for a relatively flat road. Meanwhile, Suspension type Hard very good damp vibration for high wavy road.